2001
DOI: 10.1159/000048840
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac Disease in Patients with Autoimmune Thyroiditis

Abstract: Background and Aims: The close association between coeliac disease and autoimmunity prompted us to perform an antibody screening for gluten-sensitive enteropathy in patients with autoimmune thyroid dysfunction. Methods: Sera from 220 patients with autoimmune thyroiditis, 50 euthyroid subjects with thyroid nodules and 250 blood donors were tested for IgA anti-tissue transglutaminase (anti-tTG) and antiendomysial antibodies (EmA). Results: IgA anti-tTG was positive in 7 patients with autoimmune thyroiditis, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 20 publications
0
45
2
3
Order By: Relevance
“…Additionally, in our study, the prevalence rate of CD in patients with AT was higher than in the previous studies (mean value 3.7%) [11][12][13][14] . This might be associated with the higher prevalence rate of CD in Turkish population.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Additionally, in our study, the prevalence rate of CD in patients with AT was higher than in the previous studies (mean value 3.7%) [11][12][13][14] . This might be associated with the higher prevalence rate of CD in Turkish population.…”
Section: Discussioncontrasting
confidence: 81%
“…An increased prevalence of coeliac disease has been found in patients with AT and Graves' disease [11][12][13][14] . Moreover, it has been demonstrated that many coeliacs are prone to autoimmune thyroid dysfunction [18,19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat lower than recent (smaller) studies which reported percentages between 2.7 and 4.8 (20)(21)(22)(23). We ruled out IgA-deficiency since Em and TTG test are an IgA-class test.…”
Section: Graves'contrasting
confidence: 56%
“…Estes autores recomendam a triagem de DC rotineira nos pacientes com DAT. O grupo controle deste estudo, que é de indivíduos supostamente sadios (doadores de sangue), difere do nosso, que teve base laboratorial (28).…”
Section: Discussionunclassified